Effects of endplate healing morphology on intervertebral disc degeneration after pedicle screw fixation for thoracolumbar fractures. Issue 17 (30th April 2021) - Su, Yunshan; Ren, Dong; Liu, Dehang; Li, Junfei; Wang, Tianci; Qi, Wei; Wang, Yunpeng; Chen, Yufeng; Wang, Pengcheng
Abstract : Abstract: The cartilage endplate plays an important role in the stress distribution and nutrition metabolism of the intervertebral disc. The healing morphology of the endplate after spinal fracture and its effect on the intervertebral disc degeneration are still unclear. This was a retrospective study. Patients with traumatic single-level thoracolumbar fractures treated in our orthopedic trauma service center from June 2011 to May 2019 were included and the relevant data were collected from the medical records. Based on combined computed tomography and MRI images, the endplate injury status was determined (no endplate injury, unilateral and bilateral endplate injury). According to the location of the injury, endplate injury was further divided into endplate central injury and endplate peripheral injury. The degree of posttraumatic disc lesions and disc degeneration during follow-up were classified based on the Sander classification and the Pfirrmann classification, respectively. According to the T1 image of MRI at the final follow-up, the healing morphology of endplates was determined and classified. Univariate analyses and correlation analyses were performed to evaluate the within- and between-group differences. There were in total 51 patients included in this study. Cartilage endplate fracture was significantly closely related to the degree of degeneration of the intervertebral disc ( P = .003). Injuries in different parts of the endplate have no significant effect on the intervertebral disc degeneration ( P = .204). The healing morphology after endplate fracture significantly affected the degree of intervertebral disc degeneration ( P = .001). The comparisons of groups showed that the effects of irregular healing and traumatic Schmorl nodes on disc degeneration were not statistically significant, but were significantly significant with increased curvature. These results suggest that the irregular healing and the traumatic Schmorl nodes are closely related to intervertebral disc degeneration. The presence and severity of the endplate injury can provide valuable information for individualized clinical decision-making processes.